Bio-ethanol production from sugar cane by product with cheapest strain - Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Syed Mokhtar, Sharifah Farah (2012)
S.cerevisae is the cheapest strain available for the conversion of biomass substrate where it is also capable to utilize variety of substrates. Sugar cane molasses contain 1688 g/l total sugars and it is chosen for its low cost and its effect of having high yield of ethanol. The optimization of process conditions was done with different ranges of temperature, pH, and agitation speed with fixed media compositions obtained from previous study. It was carried out by using 2 Level Factorial design formulated by Design Expert 6.0.8. Fermentation process was done in a BioSys 30 litres bioreactor for 24 hours. Product was analyzed for every 6 hours interval. 2Level Factorial design was selected to design the process in order to minimize numbers of run in bioreactor. Product analysis covers the concentration of ethanol produced and concentration of remaining sugar. Optimum conditions for highest bioethanol production using molasses are at 35 °C, pH 4.5, and 125rpm. Under this optimum operating condition the maximum of 9.31% of ethanol was produced and 34.77% of sugars were converted into ethanol. The production is acceptable theoretically as maximum ethanol production by wild type industrial yeasts can only achieves maximum up 10% v/v since greater amount of ethanol produced in the system will halt the growth of S.cerevisae. The data was validated and it was proven that the model is well fits and the findings are reliable with R2 = 99.95%. The objectives of the study were successfully achieved where the process parameters were optimized and validated.